Manajemen TIK (Teknologi Informasi dan Komunikasi) dalam Meningkatkan Mutu Pembelajaran di UPTD SD Negeri 7 Bireuen: Penelitian - Nurul Fitri Ibrahim; Aminah; Munawar (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the management of clinical supervision of school principals through coaching techniques in improving the performance of kindergarten teachers in Bireuen Regency. This study uses a qualitative descriptive approach with data collection techniques in the form of interviews, observations, and documentation studies. The results of the study indicate that clinical supervision planning is carried out through teacher needs analysis, supervision schedule preparation, and classroom observation instrument design. Organization of supervision is carried out by forming an internal supervision team and clear division of tasks. The implementation of supervision runs effectively through the application of coaching techniques, personal discussions, and direct guidance in class. Supervision evaluation is carried out periodically through reflection of supervision results and training follow-up. The implementation of clinical supervision with coaching has been proven to be able to improve teacher performance in designing, implementing, and evaluating learning.